Autism, EEG and Brain Electromagnetics Research - Hoole, P.R.P.; Pirapaharan, K.; Sofia, S.A.; Roslina, I.; Liyanage, D.L.D.A.; Senanayake, S.S.H.M.U.L.; Hoole, S.R.H. (International Conference on Biomedical Engineering and Sciences, 2012)
There has been a significant increase in the incidence of autism. We report the work on autism by our international group, on the growing attention paid to EEG based diagnosis and the interest in tracing EEG changes to brain electromagnetic signals (BEMS), seeking the cause of autism and the brain regions of its origin. The time- and frequency domain and principal component analysis (PCA) of these EEG signals with a Multilayer Perception Neural Network (MLP) identifies an autistic subject and helps improve classification accuracy. We show differences between a working brain and a relaxed brain, especially in the Alpha waves used for diagnosis.